State Capacity and Public Debt: A political economy analysis - Christoph Esslinger; Cornelius Mueller (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
High public debt combined with low capacities of the state to raise taxes and to support markets can put even developed countries into turmoil. However, the existing political economy literature of state capacity, pioneered by Besley and Persson (2009), does not investigate the interaction of these capacities with public debt. This paper studies the incentives behind raising debt and building state capacity in an integrated analytical framework. We examine the impact of political stability, cohesiveness of institutions, and income fluctuations on the political outcome, while allowing for sovereign default. We investigate when public debt and state capacity investments move in the same or opposite directions in response to exogenous parameter changes. This allows us to show when a state will simultaneously accumulate high public debt and invest only little in its capacities to raise taxes and to support markets, leading to a positive probability of sovereign default.
Keywords: H20; H60; H11; 330